A hybrid accident analysis method to assess potential navigational contingencies: The case of ship grounding. (November 2015) - Akyuz, Emre
Highlights: Application of ANP method into marine accident analysis. Quantification practice into conventional AcciMap approach. Improving safety at sea by integrating ANP method into AcciMap. Avoiding of marine accident in particular grounding in the future. Abstract: Safety is always critical aspect for marine industry since there are numerous perils at sea and those may result loss of ship, environment pollution, human injury and even loss of life. The studies show that the most of marine accidents are due to decision error (Chauvin et al., 2013) as the human factors are one of the main contributory factors of marine accident particularly grounding of ships at sea. In this context, maritime authorities struggle to decrease marine accidents at sea by enforcing rules and regulations. However, the marine accidents are still on-going. This paper primarily deals with potential navigational contingencies in particular grounding incident by proposing a hybrid accident analysis method to enhance safety in marine industry. The hybrid approach basically incorporates Accident Analyse Mapping (AcciMap) and Analytical Network Process (ANP) methods to analyse causes of marine accidents analytically. Whilst AcciMap analyses marine accident causes schematically, the ANP technique weights them analytically which can be obtained from the synthesised supermatrix. The proposed hybrid approach is demonstrated with a real-case grounding incident at sea. Thus, prominent accident causes are revealed and necessary preventive measures are proposed in advance. Consequently, the study is expected to contribute maritime safety as well as prevent grounding accidents at sea by encouraging maritime safety engineers and ship operators.